Flexible packaging film, preparation method thereof and flexible electronic device
By using elastomeric polymers with flexible and rigid segments in the packaging film of flexible electronic devices and discretely distribute polar polymer microdomains on the surface, the problem of poor bonding performance of flexible electronic devices in the deformation state is solved, and the packaging effect with high tensileability and high barrier properties is achieved.
Patent Information
- Application Number
- CN202480002600.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-04-18
AI Technical Summary
The packaging films of existing flexible electronic devices have poor adhesive properties with electronic devices under different deformation states, and lack high tensileability and high barrier properties.
A flexible encapsulated film with an elastomeric polymer having flexible segments and rigid segments as a substrate is used to improve the adhesion ability and water vapor barrier efficiency of the film by discretely distributing the polar polymer microdomains of the hard phase on the viscoplastic surface.
The tight bond between flexible packaging film and various flexible electronic device modules is realized, and it has high tensileability and high barrier properties, solving the contradiction between adhesion, barrier and stretchability in the prior art.
Smart Images

Figure CN119855869A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of packaging films, and in particular to a flexible packaging film and a preparation method thereof, and a flexible electronic device. Background Art
[0002] In flexible electronic technology, the packaging of soft electronic products currently mostly uses elastomeric sealing materials, which are characterized by the ability to deform synchronously with electronic components, so that the flexible functions of the device can be fully utilized. In order to maintain electrical performance and functional stability under various deformation states, the packaging film needs to be conformal to various components and have both stretchability and high barrier properties. Among them, stretchability can ensure that the device will not easily break or damage when it is deformed, and continue to provide effective protection for the device to adapt to different application scenarios and complex mechanical environments. High barrier performance effectively blocks the erosion of harmful substances such as moisture and oxygen in the external environment, thereby greatly extending the service life of the device. At present, ensuring that the packaging film is tightly bonded to electronic devices under different deformation states, while improving the high barrier sealing and stretchability of the packaging structure, is still a key technical problem.
[0003] Therefore, developing a flexible packaging film that can be tightly bonded to various flexible electronic device modules and has high stretchability and high barrier properties is of great significance for the packaging of flexible electronic devices.
[0004] Application Contents
[0005] One of the purposes of the embodiments of the present application is to provide a flexible packaging film and a preparation method thereof, and a flexible electronic device, aiming to solve the problems of poor adhesion between the existing packaging film and the device, poor stretchability and poor barrier properties to a certain extent.
[0006] The technical solution adopted in the embodiment of the present application is:
[0007] In a first aspect, the present application provides a flexible packaging film, wherein the flexible packaging film is based on an elastomeric polymer having a flexible segment and a rigid segment, the flexible packaging film comprises an elastomeric polymer surface and a viscoplastic surface, and hard phase polar polymer microdomains are discretely distributed in the viscoplastic surface.
[0008] In a second aspect, the present application provides a method for preparing a flexible packaging film, comprising the following steps:
[0009] The elastomeric polymer and the polar polymer are made into a mixed slurry; the elastomeric polymer has a flexible chain segment and a rigid chain segment;
[0010] The mixed slurry is deposited on the surface of a substrate and subjected to a microscopic phase separation treatment, so that the polar polymer forms a microdomain structure of a hard phase discretely distributed on the surface of one side of the film layer, and dried to obtain a flexible packaging film having an elastomeric polymer surface and a viscoplastic surface; the polar polymer microdomains are discretely distributed in the viscoplastic surface.
[0011] In a third aspect, the present application provides a flexible electronic device, wherein the flexible electronic device comprises the above-mentioned flexible packaging film and / or the flexible packaging film prepared by the above-mentioned method.
[0012] The flexible encapsulation film provided in the first aspect of the present application is based on an elastomeric polymer having a flexible segment and a rigid segment. The flexible encapsulation film has two surfaces arranged opposite to each other, one surface is an elastomeric polymer surface, which is composed of an elastomeric polymer substrate; the other surface is a viscoplastic surface, which contains a non-polar elastomeric polymer viscous molecular network and a plastic hard phase polar polymer microdomain. On the one hand, these polar polymer microdomains are partially compatible with the flexible segments in the elastomeric polymer substrate. In the phase separation process, the polar polymer microdomains enhance the π-π stacking disorder between the rigid segments as physical crosslinking points by adsorbing the flexible segments in the elastomeric polymer, so that the mobility of the bulk elastomeric polymer chain in the surface layer of the flexible encapsulation film is significantly improved. On the other hand, the polar groups in the polar polymer microdomains are highly reactive and can easily form chemical bonds with other materials to enhance the interaction between material interfaces. In the viscoplastic surface layer, the polar polymer microdomains exhibit hard phase characteristics. This ingenious fusion of soft and hard phases transforms the surface properties of the flexible encapsulation film from traditional elasticity and inertness to new properties with viscoplasticity and reactivity. Therefore, the high mobility of the elastomeric polymer molecular chains in the viscoplastic surface layer combined with the plastic hard phase polar polymer microdomains endows the flexible packaging film with excellent adhesion ability, enabling it to form a tight, strong and stretchable adhesion with various device modules and substrates without being restricted by size, material properties and geometry. At the same time, the discrete distribution of these polar polymer microdomains effectively increases the diffusion path of water molecules and improves the barrier efficiency of the flexible packaging film material to water vapor. On the other hand, the hard phase polar polymer microdomains are only distributed on the viscoplastic surface on one side of the flexible packaging film, and do not change the overall properties of the film, thereby ensuring that the mechanical properties of the flexible packaging film are maintained. This allows the flexible packaging film to be tightly bonded to various flexible electronic device modules and packaging substrates, while also having high stretchability and high barrier properties.
[0013] The preparation method of the flexible encapsulation film provided in the second aspect of the present application, after preparing the mixed slurry of the elastomeric polymer and the polar polymer, the mixed slurry is deposited on the surface of the substrate for micro-phase separation treatment. During the micro-phase separation treatment process, the polar polymer forms a micro-domain structure of the hard phase, which is affected by the elastomeric polymer to limit the growth of the micro-domain, so that the micro-domain of the polar polymer maintains a micro-nano size. The polar polymer micro-domain formed is slowly deposited on one side of the film layer under the influence of gravity, and at the same time, during the drying process of the film layer, it is affected by the rising of solvent volatilization, avoiding the aggregation of the polar polymer micro-domain into a film. Through the doping of the polar polymer micro-domain, one surface of the flexible encapsulation film has viscoplasticity, forming a viscoplastic surface, and the other surface relative to the elastomeric polymer surface. The polar polymer micro-domain has good compatibility with the flexible segment in the elastomeric polymer, which can weaken the π-π stacking between the rigid segments in the elastomeric polymer, improve the disorder of the rigid segments, promote the rearrangement of the molecular structure, form a defect-free interface between the polar polymer micro-domain and the elastomeric polymer, and significantly improve the mobility of the polymer chain on the surface of the flexible encapsulation film. In addition, the polar groups in the polar polymer microdomains are highly reactive and can easily form chemical bonds with other materials to enhance the interaction of the material interface, giving the flexible packaging film excellent adhesion and improving the barrier performance of the flexible packaging film material against water vapor. Moreover, the hard phase polar polymer microdomains are only distributed on the viscoplastic surface of one side of the flexible packaging film, and do not change the properties of the elastomeric polymer surface and the flexible packaging film as a whole, ensuring the mechanical properties of the flexible packaging film, so that the flexible packaging film can be tightly bonded to various flexible electronic device modules and packaging substrates, while also having high stretchability and high barrier properties.
[0014] The third aspect of the present application provides a flexible electronic device comprising the above-mentioned flexible packaging film, which can not only be tightly bonded to the substrate to be packaged of various modules of the flexible electronic device, but also has high stretchability and high barrier properties, effectively bridging the contradiction between adhesion, barrier properties and stretchability in the field of flexible electronic packaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or exemplary technical descriptions will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 is a schematic diagram of the structure of the flexible packaging film provided in an embodiment of the present application;
[0017] Figure 2is a schematic diagram of the functional relationship between the elastomeric polymer and the polar polymer in the flexible packaging film provided in the embodiment of the present application;
[0018] Figure 3 The diagram is an observation diagram of the surface microstructure of the flexible encapsulation film before a and after b of adding PP-g-MAH in Example 1 of the present application using an atomic force microscope (AFM); and a distribution diagram of the size of polystyrene (PS) nanodomains adjacent to the PP-g-MAH microdomains on the surface of the flexible encapsulation film before c and after d of adding PP-g-MAH;
[0019] Figure 4 is a grazing incidence wide-angle X-ray scattering (GIWAXS) spectrum of the flexible packaging film provided in Example 1 of the present application;
[0020] Figure 5 This is a test diagram of the wire drawing phenomenon on the visco-plastic surface of the flexible packaging film provided in Example 1 of the present application;
[0021] Figure 6 This is a test diagram of adhesion between the visco-plastic surface of the flexible packaging film provided in Example 1 of the present application and plastic, elastomer and hydrogel;
[0022] Figure 7 This is a comparative test chart of water vapor permeability and mechanical modulus of the flexible packaging film provided in Example 1 of the present application;
[0023] Figure 8 The test graphs show the residual surface indentation marks on the visco-plastic surface of the flexible packaging film of Example 2 of the present application and the elastomeric polymer surface of the packaging film of pure elastomeric polymer of Comparative Example 1. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present application.
[0025] It should be noted that when a component is referred to as being "fixed on" or "disposed on" another component, it may be directly on the other component or indirectly on the other component. When a component is referred to as being "connected to" another component, it may be directly or indirectly connected to the other component. The orientation or positional relationship indicated by the terms "upper", "lower", "left", "right", etc. is based on the orientation or positional relationship shown in the accompanying drawings, and is only for the convenience of description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to the specific circumstances. The terms "first" and "second" are only used for the purpose of convenience of description, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features. The meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0026] In flexible electronic technology, the packaging of soft electronic products currently mostly uses elastomeric sealing materials. In order to maintain electrical performance and functional stability under various deformation states, the packaging film needs to be conformal to various components and have both stretchability and high barrier properties. At present, ensuring that the packaging film is tightly bonded to electronic devices under different deformation states, while improving the high barrier sealing and stretchability of the packaging structure, is still a key technical challenge.
[0027] In the field of flexible electronic packaging, water and oxygen permeation caused by packaging is the main cause of device failure. Among them, the barrier to water vapor is more difficult and challenging. This is because water molecules are not only small in size, but also have strong polarity and can interact with various materials, thereby greatly increasing the possibility of their penetration. Traditional packaging materials usually use hard plastics or resins, although the intrinsic water vapor permeability of these materials can reach 10 -1 Up to 10 -2 g / m 2 / day, but this also means that the overall device can only be bent on a smaller scale at most, which cannot meet the packaging needs of some current electronic devices that are softer or even stretchable. Therefore, it is urgent to explore new packaging materials that have both excellent sealing functionality and elastic stretching properties.
[0028] There is a trade-off between the elasticity and barrier properties of polymer materials: materials with good elasticity have weak intermolecular interactions and relatively poor barrier properties; materials with dense intermolecular arrangement have high rigidity and barrier properties. Common elastomeric materials, such as silicone-based rubber (polydimethylsiloxane PDMS, Ecoflex), are widely used as substrates for various flexible and stretchable devices because of their low modulus and high elasticity. However, the molecular distance between these materials is large and the molecular chain polarity is strong, resulting in a large diffusion coefficient of water molecules in them, and the intrinsic water vapor permeability is as low as 10 2 g / m 2 / day, so it is not an ideal sealing material. In this regard, elastomers with tight molecular arrangement and non-polar polymer chains are more ideal packaging substrates. However, the non-polar molecular network cannot be tightly bonded to the device layer, and the frequent stretching of flexible electronic devices will cause interface stratification, leading to packaging failure. At present, the focus of research on the interfacial bonding problem of inert molecular networks is mostly on enhancing the interaction between interfaces by increasing the polarity of the material surface. Common methods include polymer blending modification and surface coating treatment. Although these strategies are effective in improving interfacial bonding strength, they often come at the expense of the mechanical properties and barrier properties of the material.
[0029] The fluidity of the polymer chain segments at the surface interface and the polarity of the molecules are important factors affecting the bonding strength. Among them, polymer chain segments with high fluidity can more effectively wet the bonded surface, expand the actual contact area, and improve the bonding strength; while polar molecules form chemical bonds with the surface of the bonded material to form stronger interfacial interactions. However, the increase in the fluidity of the polymer chain segments and the enhancement of the molecular polarity also promote the diffusion of water molecules, thereby reducing the barrier properties of the material. Therefore, it is urgent to develop a flexible packaging film that can be tightly bonded to various flexible electronic device modules and has high stretchability and high barrier properties.
[0030] A first aspect of the present application provides a flexible packaging film, as shown in the attached Figure 1 As shown, the flexible encapsulation film uses an elastomeric polymer having a flexible segment and a rigid segment as a substrate, and the flexible encapsulation film includes an elastomeric polymer surface and a viscoplastic surface, in which polar polymer microdomains are discretely distributed.
[0031] The flexible encapsulation film provided in the first aspect of the embodiment of the present application is based on an elastomeric polymer having a flexible segment and a rigid segment. The flexible encapsulation film has two surfaces arranged opposite to each other, one surface is an elastomeric polymer surface, which is composed of an elastomeric polymer substrate; the other surface is a viscoplastic surface, which contains a non-polar elastomeric polymer viscous molecular network and a plastic hard phase polar polymer microdomain. Among them, the polar polymer microdomain refers to a tiny particle composed of a polar polymer, and its size is usually between a few nanometers and a few microns. Polar polymers are a class of polymer materials with special properties, and their molecules contain polar bonds or polar groups, so that the entire molecule has a certain polarity. In elastomeric polymers, the flexible segment is also called a soft segment, and its molecular chain can curl and bend to a certain extent, so it has good flexibility and elasticity. The flexible segment gives the polymer material good flexibility and processing properties, so that the polymer can maintain stable performance over a wide temperature range. Rigid segments are also called hard segments, and the structures of these segments are relatively fixed, and the molecular chains are not easy to bend and curl, so they have high rigidity and strength. The presence of the rigid chain segments makes the polymer material have higher strength and hardness, and can also improve its heat resistance and chemical corrosion resistance. When the flexible packaging film of the embodiment of the present application is used, the visco-plastic surface is combined with the substrate to be packaged.
[0032] The flexible packaging film of the embodiment of the present application has at least the following performance advantages:
[0033] On the one hand, the polymer chains in the polar polymer microdomains have a certain degree of compatibility with the flexible segments in the elastomeric polymer, which is conducive to the formation of hard phase microdomains with good interfaces during the phase separation process with the main matrix of the elastomeric polymer. In addition, these polar polymer microdomains can weaken the π-π stacking between the rigid segments in the elastomeric polymer, increase the disorder of the rigid segments, and achieve partial phase separation between the elastomeric polymer matrix. The binding properties of the polar polymer microdomains and the elastomeric polymer are improved, so that a defect-free interface is formed between the polar polymer microdomains and the elastomeric polymer. At the same time, the doping of polar polymer microdomains promotes the rearrangement of the molecular structure of the surface layer of the flexible packaging film, which significantly improves the mobility of the polymer chains on the surface of the flexible packaging film. The effect of this action is shown in the attached figure. Figure 2 A schematic diagram is shown in FIG.
[0034] On the other hand, the polar groups in the polar polymer microdomains are highly reactive and can easily form chemical bonds with other materials to enhance the interaction of material interfaces. The high mobility of the elastomeric polymer molecular chains combined with the polar polymer microdomains gives the flexible packaging film excellent adhesion, allowing it to form tight, strong and stretchable adhesion with various device modules and substrates without being restricted by size, material properties and geometry. In addition, the polar polymer microdomains in the viscoplastic surface layer exhibit hard phase characteristics. This ingenious fusion of soft and hard phases transforms the surface properties of the flexible packaging film from traditional elasticity and inertness to new properties of viscoplasticity and reactivity. At the same time, the discrete distribution of these polar polymer microdomains effectively increases the diffusion path of water molecules and improves the barrier performance of the flexible packaging film material to water vapor.
[0035] On the other hand, the hard phase polar polymer microdomains are only distributed on the viscoplastic surface on one side of the flexible packaging film, and do not change the overall properties of the flexible packaging film, thereby ensuring that the mechanical properties of the flexible packaging film are maintained, so that the flexible packaging film can be tightly bonded to various flexible electronic device modules and packaging substrates, while also having high stretchability and high barrier properties.
[0036] In some possible implementations, in the flexible packaging film, the doping concentration of the polar polymer microdomain increases along the direction from the elastomeric polymer surface to the viscoplastic surface. In this case, the doping concentration of the polar polymer microdomain is high on the viscoplastic surface, ensuring that the polar polymer microdomain improves the adhesion performance and water vapor barrier performance of the flexible packaging film surface. The closer to the elastomeric polymer surface, the lower the doping concentration, and the doping of the polar polymer microdomain in the elastomeric polymer surface ensures the maintenance of the mechanical properties of the flexible packaging film.
[0037] In some possible implementations, the mass percentage of polar polymer microdomains in the flexible packaging film is 2% to 10%. Specifically, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% and other typical but non-restrictive arbitrary point values or interval values between any two point values. In this case, the polar polymer microdomains can better improve the adhesion and water vapor barrier properties of the surface of the flexible packaging film, forming a viscoplastic surface, so that it has sufficient adhesion strength to the substrate to be packaged. At the same time, it is beneficial to maintain the mechanical properties of the flexible packaging film, and avoid the excessive ratio of polar polymer microdomains to reduce the mechanical properties of the flexible packaging film.
[0038] In some possible implementations, the average particle size of the polar polymer microdomain is 50nm to 2μm. Specifically, it can be 50nm, 100nm, 200nm, 500nm, 800nm, 1000nm, 1.2μm, 1.5μm, 1.8μm, 2.0μm, and other typical but non-restrictive arbitrary point values or interval values between any two point values. In this case, the polar polymer microdomain is at the micro-nano level, which is conducive to discrete distribution in the viscoplastic surface of the flexible packaging film, improving the uniformity of polar polymer microdomain doping, fully improving the adhesion and water vapor barrier properties of the surface of the flexible packaging film, and avoiding the aggregation and sedimentation of microdomains affecting the adhesion, barrier and stretchable flexibility of the flexible packaging film.
[0039] In some possible implementations, the thickness of the flexible packaging film is 10 μm to 2 mm. Specifically, it can be 10 μm, 20 μm, 50 μm, 100 μm, 200 μm, 500 μm, 800 μm, 1000 μm, 1.2 mm, 1.5 mm, 1.8 mm, 2 mm, or any other typical but non-restrictive point value or an interval value between any two point values. In this case, the flexible packaging film has a wide thickness distribution range, which can meet the packaging application requirements of different flexible devices.
[0040] In some possible implementations, the elastomeric polymer includes a styrene block copolymer, which has excellent biocompatibility, gas barrier properties, thermal oxygen stability, and softness, and adjustable structural properties.
[0041] In some possible implementations, the elastomeric polymer includes at least one of styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-ethylene / butylene-styrene block copolymer (SEBS), styrene-ethylene / propylene-styrene block copolymer (SEPS), and styrene-isobutylene-styrene block copolymer (SIBS). Among these elastomeric polymers, styrene-based block copolymers (SBCs) composed of ethylene / propylene / butadiene / isoprene and styrene have excellent biocompatibility, gas barrier properties, thermal oxygen stability, and softness and adjustable structural properties. In some specific embodiments, the elastomeric polymer includes a styrene-isobutylene-styrene block copolymer SIBS with good thermal stability and low water vapor permeability.
[0042] In some possible implementations, the polar polymer microdomains include at least one of a maleic anhydride grafted polymer and a glycidyl ether grafted polymer.
[0043] In some possible implementations, the polar polymer microdomains include at least one of maleic anhydride grafted polyethylene (PE-g-MAH), maleic anhydride grafted polypropylene (PP-g-MAH), maleic anhydride grafted polyolefin elastomer (POE-g-MAH), glycidyl ether grafted polypropylene (PP-g-GMA), maleic anhydride grafted acrylonitrile-butadiene-styrene copolymer, and glycidyl ether grafted polypropylene. In some specific embodiments, the polar polymer microdomains include PP-g-MAH.
[0044] In some possible implementations, the selected maleic anhydride grafted polymer is closely related to its molecular structure. For example, maleic anhydride grafted polypropylene PP-g-MAH has good compatibility with the soft block portion of the elastomeric polymer, which is conducive to the formation of hard phase microdomains with good interfaces during the phase separation process with the main matrix of the elastomeric polymer. The maleic anhydride group MAH is a highly polar reactive group that can easily form chemical bonds with other materials to enhance the interaction of the material interface.
[0045] In a second aspect, an embodiment of the present application provides a method for preparing a flexible packaging film, comprising the following steps:
[0046] S10. The elastomeric polymer and the polar polymer are prepared into a mixed slurry; the elastomeric polymer has a flexible segment and a rigid segment;
[0047] S20. Depositing the mixed slurry on the surface of the substrate and performing microscopic phase separation treatment so that the polar polymer forms a hard phase microdomain structure distributed on the surface of one side of the film layer, and drying to obtain a flexible packaging film having an elastomeric polymer surface and a viscoplastic surface; the polar polymer microdomains are discretely distributed in the viscoplastic surface.
[0048] The preparation method of the flexible encapsulation film of the embodiment of the present application, after preparing the mixed slurry of the elastomeric polymer and the polar polymer, the mixed slurry is deposited on the surface of the substrate for micro-phase separation treatment. During the micro-phase separation treatment process, the polar polymer forms a micro-domain structure of the hard phase, which is affected by the elastomeric polymer to limit the growth of the micro-domain, so that the micro-domain of the polar polymer maintains a micro-nano size. The polar polymer micro-domain formed is slowly deposited on one side of the film layer under the influence of gravity, and at the same time, during the drying process of the film layer, it is affected by the rising of solvent volatilization, avoiding the aggregation of the polar polymer micro-domain into a film. Through the doping of the polar polymer micro-domain, one surface of the flexible encapsulation film has viscoplasticity, forming a viscoplastic surface, and the other surface relative to the elastomeric polymer surface. The polar polymer micro-domain has good compatibility with the flexible segment in the elastomeric polymer, which can reduce the π-π stacking between the rigid segments in the elastomeric polymer, improve the disorder of the rigid segments, promote the rearrangement of the molecular structure, form a defect-free interface between the polar polymer micro-domain and the elastomeric polymer, and significantly improve the mobility of the polymer chain on the surface of the flexible encapsulation film. In addition, the polar groups in the polar polymer microdomains are highly reactive and can easily form chemical bonds with other materials to enhance the interaction of the material interface, giving the flexible packaging film excellent adhesion and improving the barrier performance of the flexible packaging film material against water vapor. Moreover, the hard phase polar polymer microdomains are only distributed on the viscoplastic surface of one side of the flexible packaging film, and do not change the properties of the elastomeric polymer surface and the flexible packaging film as a whole, ensuring the mechanical properties of the flexible packaging film, so that the flexible packaging film can be tightly bonded to various flexible electronic device modules and packaging substrates, while also having high stretchability and high barrier properties.
[0049] In the above step S10:
[0050] In some possible implementations, the preparation method of the mixed slurry includes: a dissolution method or a melting method. In some embodiments, the elastomeric polymer is mixed with the selected polar polymer in a precise mass ratio, and then an organic solvent dissolution method or a high-temperature melting method can be selected to dissolve the mixed slurry to ensure that the two materials can be fully mixed and form a uniform solution or melt.
[0051] In some possible implementations, the steps of the dissolution method include: preparing a solution of an elastomeric polymer and a solution of a polar polymer respectively, and then blending them to obtain a mixed slurry. In this case, the elastomeric polymer and the polar polymer are dissolved in a solvent respectively, and then blended to ensure that the two materials can be fully mixed and form a uniform solution.
[0052] In some possible implementations, the concentration of the elastomeric polymer solution is 50 mg / mL to 500 mg / mL; specifically, it can be 50 mg / mL, 100 mg / mL, 150 mg / mL, 200 mg / mL, 250 mg / mL, 300 mg / mL, 350 mg / mL, 400 mg / mL, 500 mg / mL, or other typical but non-limiting arbitrary point values or an interval value between any two point values.
[0053] In some possible implementations, the concentration of the polar polymer solution is 0.5 mg / mL to 25 mg / mL; specifically, it can be 0.5 mg / mL, 1 mg / mL, 2 mg / mL, 5 mg / mL, 10 mg / mL, 15 mg / mL, 20 mg / mL, 25 mg / mL, or other typical but non-limiting arbitrary point values or an interval value between any two point values.
[0054] In the above embodiments of the present application, the concentrations of the elastomeric polymer solution and the polar polymer solution are sufficient to ensure uniform mixing of the two polymers, so that the mixed slurry has good film-forming properties. Too low or too high a concentration is likely to lead to many film-forming defects, which is not conducive to improving the gas barrier capability of the film.
[0055] In some embodiments, the steps of preparing a mixed slurry by an organic solvent dissolution method include: first, selecting a benign organic solvent such as toluene or n-hexane to thoroughly dissolve the elastomeric polymer, the mass concentration of the elastomeric polymer solution is 50mg / m-500mg / mL, the temperature is from room temperature to 80°C, and a magnetic stirrer or ultrasonic equipment is used to help dissolve to ensure that the particles are completely dissolved. Next, the polar polymer is dissolved in the same benign solvent, and the resulting solution is marked as a solution of the polar polymer, the mass concentration of which is controlled at 0.5mg / mL-25mg / mL, the temperature is 125°C to 160°C, and after it is fully dissolved, the cold water circulation is started for condensation and reflux. At room temperature, the elastomeric polymer solution is slowly poured into the polar polymer solution, and ultrasound or stirring is continued for more than 2 hours to finally obtain a uniform blended solution, i.e., a mixed slurry.
[0056] In some possible implementations, the steps of the melt method include: mixing and melting the elastomeric polymer, the plasticizer and the viscosity reducer, and then adding the polar polymer and mixing and melting to obtain a mixed slurry, wherein the plasticizer is used to increase plasticity and the viscosity reducer is used to reduce viscosity.
[0057] In some possible implementations, the temperature condition of the melt process is 140° C. to 200° C.; specifically, it may be any typical but non-limiting point value or an interval value between any two points such as 140° C., 150° C., 160° C., 170° C., 180° C., 190° C., 200° C. Under this temperature condition, the elastomeric polymer, the plasticizer and the viscosity reducer can be fully melted and mixed.
[0058] In some possible implementations, the mass ratio of the elastomeric polymer to the plasticizer and the viscosity reducer is (200-400): (20-100): (2-15). In this case, the ratio of the elastomeric polymer to the plasticizer and the viscosity reducer can prepare a mixed slurry with good processing performance and good fluidity. The plasticizer can increase the plasticity and adjust the mechanical modulus of the film; the viscosity reducer can increase the viscosity of the mixed slurry and improve the plasticity. The above ratio not only ensures the preparation of the mixed slurry, but also makes the mixed slurry have good processing performance and good fluidity, which is convenient for the subsequent film preparation of the flexible packaging film.
[0059] For example, the mass ratio of the elastomeric polymer to the plasticizer and the viscosity reducer can be 200:20:2, 300:50:10, 400:100:15, 250:30:8, 350:80:12, or any other typical but non-limiting values or an interval between any two values.
[0060] In some possible implementations, the plasticizer includes a polyisobutylene liquid rubber having an average molecular weight of 400 to 2000. Exemplarily, the average molecular weight of the polyisobutylene liquid rubber may be 400, 500, 600, 800, 1000, 1200, 1500, 1800, 2000, or any other typical but non-limiting point value or an interval value between any two point values. Under this molecular weight, the polyisobutylene liquid rubber can better adjust the plasticity of the mixed slurry, thereby improving the mechanical modulus of the flexible packaging film.
[0061] In some possible implementations, the viscosity reducer includes at least one of naphthenic oil, paraffin oil, and aromatic oil. These materials can adjust the viscosity and plasticity of the mixed slurry.
[0062] In some embodiments, a mixed slurry is prepared by a high-temperature melting method: in a reactor, the temperature is gradually raised to 140°C-200°C, and during this process, 200-400 grams of an elastomeric polymer, 20-100 grams of a plasticizer such as polyisobutylene liquid rubber with an average molecular weight of 400-2000, and 2-15 grams of a viscosity reducer such as cyclopentane oil are added. Subsequently, the stirring device is started to ensure that the materials are fully mixed during the heating process. After reaching the predetermined temperature and maintaining it for a period of time, 1-10 grams of a polar polymer is added to the reactor, and high-temperature stirring is continued until the polar polymer is completely dissolved and evenly mixed with the elastomeric polymer to form a uniform molten mixture.
[0063] In some possible implementations, the mass ratio of the elastomeric polymer to the polar polymer is (100-200): (2-10). In this case, the polar polymer microdomains can improve the adhesion and water vapor barrier properties of the surface of the flexible packaging film, forming a viscoplastic surface, so that it has sufficient adhesion strength to the substrate to be packaged. At the same time, it is beneficial to maintain the mechanical properties of the flexible packaging film, and avoid the excessive ratio of the polar polymer microdomains to reduce the mechanical properties of the flexible packaging film.
[0064] For example, the mass ratio of the elastomeric polymer to the polar polymer can be 100:2, 120:3, 150:5, 180:8, 100:5, 100:8, 100:10, 200:10, or any other typical but non-limiting value or an interval between any two values.
[0065] In some possible implementations, the elastomeric polymer includes at least one of styrene-butadiene-styrene, styrene-isoprene-styrene, styrene-ethylene-butylene-styrene, styrene-isobutylene-styrene, styrene-propylene-styrene, and styrene-ethylene-propylene-styrene. These elastomeric polymers all have excellent biocompatibility, gas barrier properties, thermal oxygen stability, and are soft and have adjustable structural properties. In some specific embodiments, the elastomeric polymer includes a styrene-isobutylene-styrene block copolymer SIBS with good thermal stability and low water vapor permeability.
[0066] In some possible implementations, the polar polymer includes at least one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted acrylonitrile-butadiene-styrene copolymer, and glycidyl ether grafted polypropylene. These polar polymers have high compatibility with elastomeric polymers, which is conducive to forming hard phase microdomains with good interfaces during phase separation with the main matrix of the elastomeric polymer. And it has a strong polar reactive group, which is easy to form chemical bonds with other materials to enhance the interaction of the material interface. In some specific embodiments, the polar polymer microdomain includes PP-g-MAH.
[0067] In the above step S20: first, a suitable substrate must be selected, and then the above precursor mixed solution is evenly poured onto the substrate. During this process, various film-forming conditions must be strictly controlled to achieve microscopic phase separation of the elastomeric polymer and the polar polymer to form a flexible packaging film having an elastomeric polymer surface and a viscoplastic surface.
[0068] In some possible implementations, the substrate is pre-treated with plasma to improve its surface hydrophilicity.
[0069] In some possible implementations, plasma pretreatment uses an argon-oxygen mixed gas, the excitation frequency is 10 MHz to 15 MHz, and the treatment time is 5 min to 15 min. Under this condition, the hydrophilicity of the substrate can be fully improved. Exemplarily, the excitation frequency of the plasma pretreatment substrate can be 10 MHz, 11 MHz, 12 MHz, 13 MHz, 14 MHz, 15 MHz, etc., typical but non-limiting arbitrary point values or interval values between any two point values; the treatment time can be 5 min, 8 min, 10 min, 12 min, 15 min, etc., typical but non-limiting arbitrary point values or interval values between any two point values.
[0070] In some specific embodiments, a suitable substrate is selected, such as a glass plate or a glass watch glass. The surface of the substrate should be flat, clean, free of oil and dust, and can be plasma pretreated to improve its surface hydrophilicity, wherein the plasma pretreatment gas is an argon-oxygen mixed gas, the excitation frequency is 10 MHz-15 MHz, and the treatment time is 5 min-15 min.
[0071] In some possible implementations, the method of depositing the mixed slurry on the surface of the substrate includes solution casting, blade coating or extrusion coating. In this case, the mixed slurry prepared by the solution method is suitable for preparing a film layer by solution casting or blade coating; for the mixed slurry prepared by the high temperature melting method, the extrusion coating method can be used for film formation to ensure the uniformity of the film thickness.
[0072] In some possible implementations, the step of micro-phase separation treatment includes: after sealing and standing for 3h to 6h, volatilizing and removing the solvent in the mixed slurry at an evaporation rate of 0.4μm / min to 0.7μm / min. In this case, during the sealing and standing process, the polar polymer forms a micro-domain structure, and the growth of the micro-domain is limited by the influence of the elastomeric polymer, so that it maintains a micro-nano size; the formed micro-domain is slowly deposited to one side of the film layer under the influence of gravity. In the process of solvent volatilization, the micro-domains are distributed in a gradient in the film layer due to the influence of the rising solvent volatilization, forming a viscoplastic surface on one surface of the flexible packaging film. The distribution of polar polymer micro-domains formed in the elastomeric polymer matrix depends on the phase separation between it and the main matrix and the experimental condition control under the corresponding film forming conditions. During the film-forming process, if the standing sealing time of the mixed slurry is too short or the evaporation rate is too fast, the phase separation between the elastomeric polymer and the polar polymer will not be complete. If the standing sealing time is too long or the evaporation rate is too short, the microdomains formed by the polar polymer will completely settle and stratify at the bottom. Under these two experimental conditions, a viscoplastic surface layer cannot be obtained.
[0073] Exemplarily, the sealed standing time of the microphase separation treatment can be 3h, 4h, 5h, 6h, etc., typical but non-limiting arbitrary point values or an interval value between any two point values, and the evaporation rate can be 0.4, 0.5, 0.6, 0.7, etc., typical but non-limiting arbitrary point values or an interval value between any two point values.
[0074] In some possible implementations, the drying conditions include: drying under vacuum conditions at a temperature of 80°C to 120°C for 12 hours to 24 hours. Exemplarily, the drying temperature may be any typical but non-limiting point value or an interval value between any two point values, such as 80°C, 90°C, 100°C, 110°C, 120°C, etc., and the drying time may be any typical but non-limiting point value or an interval value between any two point values, such as 12 hours, 15 hours, 18 hours, 20 hours, 24 hours, etc. In this case, the solvent component in the film layer can be removed without affecting the performance of the flexible packaging film.
[0075] In some possible implementations, the mixed slurry is deposited on the surface of the substrate by solution casting, and a microscopic phase separation treatment is performed. The steps of drying to obtain a flexible encapsulation film having an elastomeric polymer surface and a viscoplastic surface include: first, pouring the mixed slurry into a glass culture dish pretreated with plasma. After being sealed with aluminum foil and standing for 3h to 6h at room temperature, the evaporation rate of the solvent is controlled to 0.4μm / min to 0.7μm / min by making tiny pinholes on the aluminum foil. Subsequently, the organic solvent is allowed to evaporate slowly in a fume hood. In this process, it is necessary to finely control the condition parameters such as the concentration ratio of the reactants, the type of solvent, and the evaporation rate of the solvent to control the degree and rate of phase separation and ensure that the film thickness is uniformly controlled at 0.25mm-1.2mm. After drying, the film is slowly peeled off from the culture dish and placed in a vacuum oven for 12 hours to completely remove the residual solvent to obtain a flexible film.
[0076] In some possible implementations, the mixed slurry is deposited on the surface of the substrate by a scraping film forming method, a microscopic phase separation treatment is performed, and the steps of drying to obtain a flexible encapsulation film having an elastomeric polymer surface and a viscoplastic surface include: first, the mixed slurry is sealed for 3 hours to 6 hours, and then the mixed slurry is evenly coated on a glass plate pretreated with plasma using a scraper or a scraper. During the coating process, the angle and pressure between the scraper and the substrate surface need to be precisely controlled to ensure the uniformity of the coating and the required thickness. The coating speed can be adjusted according to the viscosity of the solution and the required film thickness. After coating, the substrate is placed in a dry environment and the solvent is slowly evaporated at an evaporation rate of 0.4μm / min to 0.7μm / min. After the drying process is completed, the film is slowly peeled off from the substrate, and finally stored in a vacuum oven for 12 hours to remove the residual solvent to obtain a flexible film.
[0077] In some possible implementations, the mixed slurry after scraping is placed horizontally in an atmosphere filled with saturated toluene or other solvent vapor, left to stand, then taken out and the solvent is allowed to evaporate naturally at room temperature. The mixed slurry for scraping film contains a certain proportion of volatile solvents. In a normal atmospheric environment, the solvent will continue to evaporate, causing the solution concentration to gradually increase, and the evaporation rate will also change as the solvent decreases. However, in a saturated steam atmosphere, since the ambient vapor pressure and the solution surface vapor pressure are close to equilibrium, the evaporation of the solvent is suppressed, and slowing down the evaporation rate can allow the precursor solution after scraping to have more time for leveling, diffusion and chemical reaction, thereby forming a more uniform and dense film layer.
[0078] In some possible implementations, the mixed slurry is deposited on the surface of a substrate by extrusion coating, subjected to microscopic phase separation treatment, and dried to obtain a flexible encapsulation film having an elastomeric polymer surface and a viscoplastic surface. The steps include: first, the mixed slurry prepared by high-temperature melting is melted by heating, and then uniformly extruded and coated on a polytetrafluoroethylene (PTFE) substrate, and precisely controlled to ensure the uniformity of the coating thickness. Subsequently, the coated substrate is slowly cooled to 100°C and kept at this temperature for 1h-4h. Next, a traction device is used to smoothly transfer the melt to a 20°C environment for rapid cooling. Finally, the naturally cooled film is peeled off from the substrate with the help of the spraying of an ethanol solution to obtain a flexible film.
[0079] In some possible implementations, the thickness of the film prepared by extrusion coating must be strictly controlled to no more than 120 microns to ensure that the required viscoplastic surface layer can be formed. A film that is too thick will not achieve the expected surface viscoplastic properties. As the thickness of the film layer gradually increases, the degree of freedom of the surface molecular chains in the direction perpendicular to the film plane increases accordingly. In the case of thicker film layers, the surface constraints of the molecular chains in the area away from the substrate surface are significantly reduced, resulting in an increase in the degree of entanglement of these chain segments. This increase in entanglement may extend the diffusion path of the molecular chains in the surface layer close to the substrate. On the contrary, when the thickness of the film layer decreases, the diffusion rate of the molecular chains close to the bottom surface may increase, thereby promoting the compatibility between the polar microregions and the elastomeric polymer substrate, and by adjusting the conformation of the molecular chains on the bottom surface, giving the material surface viscoplastic properties.
[0080] In some possible implementations, when a high-temperature molten mixture is used to prepare a film layer by extrusion coating, the methods for regulating the phase separation of polar polymer microdomains and the main elastomeric polymer include: changing the extrusion speed and pressure can affect the flow state and phase separation process of the polymer. Higher extrusion speeds and pressures may subject the polymer molecular chains to greater shear forces, promoting the occurrence of phase separation. However, excessive speeds and pressures may also cause defects in the film layer, such as uneven thickness and rough surface. In addition, the cooling rate after extrusion also has an important influence on phase separation. A faster cooling rate can make the polymer solidify quickly, restrict the movement of the molecular chains, and thus reduce the degree of phase separation, while a slower cooling rate can give the molecular chains more time to adjust and separate.
[0081] In a third aspect, an embodiment of the present application provides a flexible electronic device, wherein the flexible electronic device comprises the above-mentioned flexible packaging film and / or the flexible packaging film prepared by the above-mentioned method.
[0082] The flexible electronic device of the embodiment of the present application includes the above-mentioned flexible packaging film, which can be tightly bonded to the substrate to be packaged of various modules of the flexible electronic device, and at the same time has high stretchability and high barrier properties, effectively bridging the contradiction between adhesion, barrier and stretchability in the field of flexible electronic packaging. Good adhesion can ensure that the packaging film is closely attached to the surface of the device, is not easy to fall off or break when subjected to external force, can maintain the integrity of the packaging structure, effectively prevent moisture, oxygen and other pollutants from entering the inside of the device, thereby protecting the device from damage and improving the reliability of the package. The packaging film with excellent stretchability can adapt to various deformations of the flexible electronic device during use without causing damage to the packaging structure or performance degradation, better withstand mechanical stress, reduce problems such as film cracking and falling off caused by deformation, thereby improving the durability of the flexible electronic device. Airtightness can effectively prevent small molecules such as water vapor and oxygen from invading the inside of the device, avoid corrosion or oxidation of the circuit, thereby extending the service life of the device, reducing performance fluctuations caused by environmental factors (such as humidity and temperature changes), and improving the reliability and stability of the flexible electronic device.
[0083] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to demonstrate the significant improvement in performance of the flexible packaging film and preparation method thereof, and the flexible electronic device of the embodiments of the present application, the above technical solutions are illustrated by means of multiple embodiments below.
[0084] Example 1
[0085] A flexible packaging film, a method for preparing a stretchable high-barrier packaging film with surface viscoplasticity by solution casting, comprising the following steps: first, dissolving 1g of PP-g-MAH (maleic anhydride grafted polypropylene) particles in 200ml of toluene solution, stirring at 130°C for 2 hours, and using circulating water for condensation reflux. After PP-g-MAH is completely dissolved, 50g of SIBS (styrene-isobutylene-styrene block copolymer) masterbatch is added to the solution, and stirring is continued at 85°C for 3 hours. Next, a certain mass of the above-mentioned PP-g-MAH / SIBS precursor mixed solution is poured into a glass culture dish pretreated with oxygen plasma. Then, the culture dish is sealed with aluminum foil at room temperature and left to stand for 4 hours. The evaporation rate of the solvent is finely controlled to be 0.4μm / min to 0.7μm / min by making tiny pinholes on the aluminum foil, and then the culture dish is placed horizontally in a fume hood to allow the toluene solvent to evaporate slowly. After the solvent was evaporated, the flexible encapsulation film was gently peeled off from the culture dish and stored in a vacuum oven at 100° C. for 12 hours to remove the residual solvent, thereby obtaining a flexible encapsulation film in which the average particle size of the polar polymer microdomains was 550 nm and the mass percentage was 2%.
[0086] Example 2
[0087] A flexible packaging film, a method for preparing a stretchable high-barrier packaging film with surface viscoplasticity by a scraping film-forming method, comprising the following steps: first, dissolving 5 grams of PP-g-MAH particles in 400 ml of toluene solution, the process is carried out at 130°C, and stirring is continued for 2 hours, during which condensation and reflux are performed through a circulating water system to obtain solution A. Dissolve 200 grams of SIBS raw material in 1000 ml of n-hexane solution, and continue to stir until completely dissolved to obtain solution B. Mix solution A with solution B to form a uniform and viscous mixed solution. In a dust-free environment, pour the mixed solution on a plasma-pretreated glass substrate and scrape it evenly with a scraper. During the scraping process, the scraping speed and pressure are precisely controlled to ensure the uniformity of the coating and achieve the desired thickness. Subsequently, the scraped substrate is horizontally placed in an atmosphere filled with saturated toluene vapor, left to stand for 2 hours, then taken out and the solvent is allowed to evaporate naturally at room temperature. After the drying process, the film was slowly peeled off from the substrate and placed in a vacuum oven for 12 hours to completely remove the residual solvent, thereby obtaining a flexible encapsulation film in which the average particle size of the polar polymer microdomains was 90 nm and the mass percentage was 2.5%.
[0088] Example 3
[0089] A flexible packaging film, a method for preparing a stretchable high-barrier packaging film with surface viscoplasticity by extrusion coating, comprising the following steps: first, 200 grams of SIBS masterbatch, 30 grams of polyisobutylene liquid (PB 1300) and 8 grams of cyclohexane oil are added to a reactor at one time, and then the temperature is gradually raised to 170°C. During this period, a stirring device is started to ensure that the materials are fully mixed during the heating process. When the predetermined temperature is reached, it is maintained for 45 minutes, and then 4 grams of PP-g-MAH is added to the reactor, and high-temperature stirring is continued until a uniform molten mixture is formed. Next, the prepared rubber is heated and melted, and uniformly coated on a PTFE substrate by an extrusion coater. During the coating process, the coating parameters need to be accurately controlled to ensure the consistency of the coating thickness. After the coating is completed, the substrate is slowly cooled to 100°C and kept at this temperature for 1 hour to ensure uniform solidification of the rubber. Thereafter, the substrate is smoothly transferred to an environment of 20°C by a traction device for rapid cooling. Finally, with the assistance of ethanol solution, the naturally cooled film was peeled off from the substrate to obtain a flexible packaging film, in which the average particle size of the polar polymer microdomains was 80 nm and the mass percentage was 1.7%.
[0090] Example 4
[0091] A flexible packaging film, which is different from the first embodiment in that the polar polymer is styrene-ethylene / butylene-styrene block copolymer (SEBS).
[0092] The method comprises the following steps: first, dissolving 1 g of PP-g-MAH in 200 ml of toluene solution, stirring at 130°C for 2 hours, and using circulating water for condensation and reflux. After PP-g-MAH is completely dissolved, 75 g of SEBS masterbatch is added to the solution, and stirring is continued at 80°C for 1 hour. Next, a certain mass of the above-mentioned PP-g-MAH / SEBS precursor mixed solution is poured into a glass culture dish pretreated with oxygen plasma. Then, the culture dish is sealed with aluminum foil at room temperature and left to stand for 3 hours. The evaporation rate of the solvent is finely controlled to be 0.4 μm / min to 0.7 μm / min by making tiny pinholes on the aluminum foil, and then the culture dish is placed horizontally in a fume hood to allow the toluene solvent to evaporate slowly. After the solvent was evaporated, the flexible encapsulation film was gently peeled off from the culture dish and stored in a vacuum oven at 100° C. for 12 hours to remove the residual solvent, thereby obtaining a flexible encapsulation film in which the average particle size of the polar polymer microdomains was 380 nm and the mass percentage was 1.3%.
[0093] Example 5
[0094] A flexible packaging film, which is different from Example 1 mainly in that the polar polymer is styrene-ethylene / propylene-styrene block copolymer (SEPS).
[0095] The method comprises the following steps: first, dissolving 1 g of PP-g-MAH in 200 ml of toluene solution, stirring at 130°C for 2 hours, and using circulating water for condensation and reflux. After PP-g-MAH is completely dissolved, 50 g of SEPS masterbatch is added to the solution, and stirring is continued at 80°C for 1 hour. Next, a certain mass of the PP-g-MAH / SEPS precursor mixed solution is poured into a glass culture dish pretreated with oxygen plasma. Then, the culture dish is sealed with aluminum foil at room temperature and left to stand for 3 hours. The evaporation rate of the solvent is finely controlled to be 0.4 μm / min to 0.7 μm / min by making tiny pinholes on the aluminum foil, and then the culture dish is placed horizontally in a fume hood to allow the toluene solvent to evaporate slowly. After the solvent was evaporated, the flexible encapsulation film was gently peeled off from the culture dish and stored in a vacuum oven at 100° C. for 12 hours to remove the residual solvent, thereby obtaining a flexible encapsulation film in which the average particle size of the polar polymer microdomains was 350 nm and the mass percentage was 2%.
[0096] Example 6
[0097] A flexible packaging film, which is different from the embodiment 1 mainly in that the polar polymer is styrene-butadiene-styrene block copolymer (SBS).
[0098] The method comprises the following steps: first, dissolving 1 g of PP-g-MAH particles in 200 ml of toluene solution, stirring at 130° C. for 2 hours, and using circulating water for condensation and reflux. After PP-g-MAH is completely dissolved, 50 g of SBS masterbatch is added to the solution, and stirring is continued at 80° C. for 1 hour. Next, a certain mass of the PP-g-MAH / SBS precursor mixed solution is poured into a glass culture dish pretreated with oxygen plasma. Then, the culture dish is sealed with aluminum foil at room temperature and left to stand for 3 hours. The solvent evaporation rate is finely controlled to be 0.4 μm / min to 0.7 μm / min by making tiny pinholes on the aluminum foil, and then the culture dish is placed horizontally in a fume hood to allow the toluene solvent to evaporate slowly. After the solvent is evaporated, the flexible encapsulation film is gently peeled off from the culture dish and stored in a vacuum oven at 100° C. for 12 hours to remove the residual solvent. A flexible packaging film is obtained, wherein the average particle size of polar polymer microdomains is 260nm and the mass percentage is 2%.
[0099] Example 7
[0100] A flexible packaging film, which is different from Example 1 mainly in that the polar polymer is styrene-isoprene-styrene block copolymer (SIS).
[0101] The method comprises the following steps: first, dissolving 1 g of PP-g-MAH particles in 200 ml of toluene solution, stirring at 120° C. for 2 hours, and using circulating water for condensation and reflux. After PP-g-MAH is completely dissolved, 50 g of SIS masterbatch is added to the solution, and stirring is continued at 80° C. for 1 hour. Next, a certain mass of the PP-g-MAH / SIS precursor mixed solution is poured into a glass culture dish pretreated with oxygen plasma. Then, the culture dish is sealed with aluminum foil at room temperature and left to stand for 3 hours. The evaporation rate of the solvent is finely controlled to be 0.4 μm / min to 0.7 μm / min by making tiny pinholes on the aluminum foil, and then the culture dish is placed horizontally in a fume hood to allow the toluene solvent to evaporate slowly. After the solvent is evaporated, the flexible encapsulation film is gently peeled off from the culture dish and stored in a vacuum oven at 100° C. for 12 hours to remove the residual solvent. A flexible packaging film is obtained, wherein the average particle size of polar polymer microdomains is 90nm and the mass percentage is 2%.
[0102] Example 8
[0103] A flexible packaging film, which is different from Example 1 mainly in that the elastomeric polymer is maleic anhydride grafted polyethylene (PE-g-MAH).
[0104] The method comprises the following steps: first, dissolving 2 g of PE-g-MAH particles in 200 ml of toluene solution, stirring at 130°C for 2 hours, and using circulating water for condensation and reflux. After PE-g-MAH is completely dissolved, 50 g of SIBS masterbatch is added to the solution, and stirring is continued at room temperature for 1 hour. Next, a certain mass of the above-mentioned PE-g-MAH / SIBS precursor mixed solution is poured into a glass culture dish pretreated with oxygen plasma. Then, the culture dish is sealed with aluminum foil at room temperature and left to stand for 3 hours. The evaporation rate of the solvent is finely controlled to 0.4 μm / min to 0.7 μm / min by making tiny pinholes on the aluminum foil, and then the culture dish is placed horizontally in a fume hood to allow the toluene solvent to evaporate slowly. After the solvent is evaporated, the flexible encapsulation film is gently peeled off from the culture dish and stored in a vacuum oven at 100°C for 12 hours to remove the residual solvent. A flexible packaging film is obtained, wherein the average particle size of polar polymer microdomains is 800nm and the mass percentage content is 4%.
[0105] Example 9
[0106] A flexible packaging film, which is different from Example 1 mainly in that the elastomeric polymer adopts maleic anhydride grafted polyolefin elastomer (POE-g-MAH).
[0107] The method comprises the following steps: first, dissolving 2 g of POE-g-MAH particles in 200 ml of toluene solution, stirring at 130 ° C for 2 hours, and using circulating water for condensation and reflux. After POE-g-MAH is completely dissolved, 50 g of SIBS masterbatch is added to the solution, and stirring is continued at room temperature for 1 hour. Next, a certain mass of the POE-g-MAH / SIBS precursor mixed solution is poured into a glass culture dish pretreated with oxygen plasma. Then, the culture dish is sealed with aluminum foil at room temperature and left to stand for 3 hours. The evaporation rate of the solvent is finely controlled to 0.4 μm / min to 0.7 μm / min by making tiny pinholes on the aluminum foil, and then the culture dish is placed horizontally in a fume hood to allow the toluene solvent to evaporate slowly. After the solvent is evaporated, the flexible encapsulation film is gently peeled off from the culture dish and stored in a vacuum oven at 100 ° C for 12 hours to remove the residual solvent. A flexible packaging film is obtained, wherein the average particle size of polar polymer microdomains is 680nm and the mass percentage is 4%.
[0108] Example 10
[0109] A flexible packaging film, which is different from Example 1 mainly in that the elastomeric polymer adopts polyolefin elastomer grafted with glycidyl ether (POE-g-GMA).
[0110] The method comprises the following steps: first, dissolving 2 g of POE-g-GMA particles in 200 ml of toluene solution, stirring at 120° C. for 2 hours, and using circulating water for condensation and reflux. After POE-g-GMA is completely dissolved, 40 g of SIBS masterbatch is added to the solution, and stirring is continued at room temperature for 1 hour. Next, a certain mass of the POE-g-GMA / SIBS precursor mixed solution is poured into a glass culture dish pretreated with oxygen plasma. Then, the culture dish is sealed with aluminum foil at room temperature and left to stand for 3 hours. The evaporation rate of the solvent is finely controlled to 0.4 μm / min to 0.7 μm / min by making tiny pinholes on the aluminum foil, and then the culture dish is placed horizontally in a fume hood to allow the toluene solvent to evaporate slowly. After the solvent is evaporated, the flexible encapsulation film is gently peeled off from the culture dish and stored in a vacuum oven at 100° C. for 12 hours to remove the residual solvent. A flexible packaging film is obtained, wherein the average particle size of polar polymer microdomains is 80nm and the mass percentage is 5%.
[0111] Embodiment 11
[0112] A flexible packaging film, which is different from Example 1 mainly in that the concentration ratio of PP-g-MAH is increased so that the mass percentage of polar polymer microdomains in the prepared flexible packaging film is 5%.
[0113] Example 12
[0114] A flexible packaging film, which is different from Example 1 mainly in that the concentration ratio of PP-g-MAH is increased so that the mass percentage of polar polymer microdomains in the prepared flexible packaging film is 7.5%.
[0115] Embodiment 13
[0116] A flexible packaging film, which is different from Example 1 mainly in that the concentration ratio of PP-g-MAH is reduced so that the mass percentage of polar polymer microdomains in the prepared flexible packaging film is 1%.
[0117] Embodiment 14
[0118] A flexible packaging film, which is different from Example 1 mainly in that the concentration ratio of PP-g-MAH is increased so that the mass percentage of polar polymer microdomains in the prepared flexible packaging film is 11%.
[0119] Comparative Example 1
[0120] A flexible packaging film, a method for preparing a packaging film of a pure elastomeric polymer by a scraping film-forming method, comprising the following steps: first, dissolving 200 grams of SIBS raw material in 1000 ml of n-hexane solution, and continuously stirring until completely dissolved to obtain solution B. In a dust-free environment, pour the mixed solution on a glass substrate pretreated by plasma, and scrape it evenly with a scraper. During the scraping process, the scraping speed and pressure are precisely controlled to ensure the uniformity of the coating and to achieve the expected thickness. Subsequently, the scraped substrate is horizontally placed in an atmosphere filled with saturated toluene vapor, left to stand for 2 hours, then taken out and the solvent is allowed to evaporate naturally at room temperature. After the drying process is completed, the film is slowly peeled off from the substrate, and placed in a vacuum oven for 12 hours to completely remove the residual solvent, thereby obtaining a flexible packaging film.
[0121] Comparative Example 2
[0122] A flexible packaging film, a method for preparing polar polymer microdomains uniformly and discretely distributed throughout the packaging film by a scraping film forming method, comprising the following steps: first, dissolving 5 grams of PP-g-MAH particles in 400 ml of toluene solution, the process is carried out at 130°C, and stirring is continued for 2 hours, during which condensation and reflux are performed through a circulating water system to obtain solution A. Dissolving 200 grams of SIBS raw material in 1000 ml of n-hexane solution, stirring continuously until completely dissolved to obtain solution B. Mixing solution A with solution B to form a uniform and viscous mixed solution. In a dust-free environment, pouring the mixed solution on a plasma pretreated glass substrate, and scraping it uniformly with a scraper. During the scraping process, the scraping speed and pressure are precisely controlled to ensure the uniformity of the coating and to achieve the expected thickness. Subsequently, the scraped substrate is horizontally taken out and the solvent is allowed to evaporate naturally at room temperature. After the drying process is completed, the film is slowly peeled off from the substrate and placed in a vacuum oven for 12 hours to completely remove the residual solvent.
[0123] Comparative Example 3
[0124] A flexible encapsulation film, a method for preparing a polar polymer deposition to form a polar polymer layer by a scraping film forming method, comprising the following steps: first, dissolving 5 grams of PP-g-MAH particles in 400 ml of toluene solution, the process is carried out at 130°C, and stirring is continued for 2 hours, during which condensation and reflux are performed through a circulating water system to obtain solution A. Dissolving 200 grams of SIBS raw material in 1000 ml of n-hexane solution, stirring continuously until completely dissolved to obtain solution B. Mixing solution A with solution B to form a uniform and viscous mixed solution. In a dust-free environment, pouring the mixed solution on a plasma pretreated glass substrate, and scraping it evenly with a scraper. During the scraping process, the scraping speed and pressure are precisely controlled to ensure the uniformity of the coating and to achieve the expected thickness. Subsequently, the scraped substrate is horizontally placed in an atmosphere filled with saturated toluene vapor, left to stand for 12 hours, and then taken out and the solvent is allowed to evaporate naturally at room temperature. After the drying process is completed, the film is slowly peeled off from the substrate and placed in a vacuum oven for 12 hours to completely remove the residual solvent.
[0125] In order to verify the progress of the embodiments of the present application, the following performance tests were performed on the above embodiments and comparative examples:
[0126] 1. Characterize the structure of the sample prepared in Example 1:
[0127] The surface microstructure of the flexible encapsulation film before and after adding PP-g-MAH was observed using an atomic force microscope (AFM). Figure 3 The results show that the size distribution of polystyrene (PS) nanodomains adjacent to PP-g-MAH microdomains has changed significantly, which confirms that the introduction of PP-g-MAH microdomains has led to the rearrangement of the molecular chains in the SIBS surface layer composed of PS hard phase and PIB soft phase.
[0128] In addition, from the attached Figure 4 The grazing incidence wide angle X-ray scattering (GIWAXS) spectrum in the figure shows the disappearance of the two characteristic scattering peaks originally belonging to PS, which confirms at the molecular scale that the introduction of PP-g-MAH microdomains makes the PS nanodomain structure more disordered. Since PS nanodomains act as physical crosslinkers in the SIBS network, the reduction in their size and order will significantly increase the mobility of the surface polymer chains, thereby making the surface of the flexible encapsulation film exhibit sticky properties.
[0129] In addition, the hard phase PP-g-MAH embedded in the viscoplastic surface plays a toughening role. When we gently press the two surface layers and slowly peel them off, we can observe obvious surface drawing phenomenon; while the surface of the elastomeric polymer without polar polymer microdomains has no surface drawing phenomenon ( Figure 5 ), which highlights the visco-plastic deformation behavior of the surface layer.
[0130] 2. Characterization of the interfacial adhesion properties of the samples prepared in Example 1:
[0131] As attached Figure 6 The excellent performance of flexible encapsulation films with surface viscoplasticity when adhering to plastics, elastomers and hydrogels, including their bendability, stretchability and stability, is fully demonstrated. Figure 6 (a) shows the interface between the film and the polyethylene terephthalate (PET) substrate, which remains tightly adhered after 7 days of bending treatment and water immersion. Figure 6 Figure b shows the interface between the film and the silicone rubber Ecoflex, which can achieve a stretchability of 280% and remain stable after being immersed in acidic or alkaline solutions for more than 15 days. Figure 6 Figure c shows that the interface between the film and the polyvinyl alcohol (PVA) hydrogel is tightly attached, and even when the hydrogel is dried and wrinkled due to volume shrinkage, the interface between the two can still maintain tight adhesion. These results prove that the prepared surface viscoplastic flexible encapsulation film can form conformal, tough and stretchable adhesion with various device modules and substrates.
[0132] 3. Characterization of the mechanical properties and water vapor barrier properties of the samples prepared in Example 1:
[0133] Figure 7 Figure a shows the comparison of water vapor permeability and mechanical modulus of different flexible packaging films, where plastics are plastic polymer materials, including PC (polycarbonate), PI (polyimide), PVC (polyvinyl chloride), PET (polyethylene terephthalate), PS (polystyrene plastics), LDPF (low-density polyethylene), PEN (polyethylene naphthalate), PVDC (polyvinylidene chloride), PVDF (polyvinylidene fluoride), HDPE (high-density polyethylene), Parylenc C (polyparadichlorotoluene) DENG; elastomers are elastomers, including PDMS (polydimethylsiloxane), IIR (butyl rubber), POE (polyolefin elastomer), SEBS (styrene-ethylene-butylene-styrene block copolymer), PIB (polyisobutylene), etc. The water vapor permeability of the flexible packaging film with surface viscoplasticity under the same test conditions is only 0.09g / m 2 / day, which is comparable to some high barrier plastics such as Parylenc C, showing excellent barrier effect. Figure 7 Figure b shows the comparison of mechanical curves with and without PP-g-MAH microdomains, indicating that the formation of the viscoplastic surface layer has no effect on the overall mechanical properties of the flexible packaging film. Figure 7Figure c compares the changes in barrier properties of flexible packaging films with a thickness of 0.25 mm and viscoplastic surface properties after different stretching cycles. The results show that even after millions of cyclic stretching, the water vapor transmission rate remains stable, which proves that under large deformation conditions, the film can still maintain its reliable barrier properties.
[0134] 4. The viscoplastic surface of the flexible packaging film prepared by large-area scraping method in Example 2 and the elastomeric polymer surface of the packaging film of pure elastomeric polymer prepared by large-area scraping method in Comparative Example 1 were tested for the residual surface indentation marks. Figure 8 As shown in the figure, i→ii→iii are before the indentation needle applies pressure→during the indentation needle applies pressure→after the indentation needle applies pressure. The experimental results clearly reveal the elastic properties of the surface of the pure elastomeric polymer, while the elastomer with a viscoplastic surface adheres to the indentation needle and is accompanied by obvious fragmentation after the indentation needle applies pressure. This observation provides intuitive and strong evidence for the existence of surface viscoplasticity.
[0135] 5. The water vapor barrier performance, stretchability, and adhesion ability of the viscoplastic surface of the flexible packaging films prepared in the above embodiments and comparative examples were tested respectively:
[0136] ① Water vapor barrier performance test (water vapor transmission rate): The test was conducted using the AQUATRAN 3 water vapor transmission rate equipment from Mocon (USA), with a test range of 0.00005 to 5 g / m 2 / day(test area 50cm 2 ), temperature range: 10~40℃, humidity range: 5~90%RH, 100%RH. The specific operation process is as follows: First, clamp the film to be tested in the test chamber, use dry nitrogen to remove the moisture in the test chamber, and then introduce pure dry carrier gas to the infrared sensor to produce a stable zero value; then, control the temperature at 38℃ and the humidity at 90%RH, input water vapor to the outer end of the test chamber, and the water molecules penetrate into the inner end of the test chamber through the tested sample, and the flowing dry carrier gas conducts the infiltrated water molecules to the infrared sensor; finally, the infrared sensor senses the proportion of water molecules, generates current and inputs it into the load resistor, and the computer software calculates the precise water vapor transmission rate value based on the change in current and resistance.
[0137] ②Stretchability test (Young's modulus): The stress-strain curve was measured using a CMT6203 universal testing machine equipped with a 100N load cell. The film samples were cut into dumbbells with a width of 5mm and a length of 80mm using a customized small punching machine. The tensile speed was maintained at 100mm / min during the test, and each group of samples was kept parallel at least five times, and the results were averaged.
[0138] ③ Adhesion ability test of visco-plastic surface (interface peel strength): At room temperature, the visco-plastic surface of the film sample is bonded to the PET plastic substrate. The specific process is as follows: First, ensure that the surface of the film and plastic substrate to be laminated is clean, free of dust, oil or other impurities; then, place the film and plastic substrate in the working area of the vacuum laminator according to the predetermined lamination order, and perform lamination for 3 minutes at 125°C and 70kPa. After lamination, wait for the sample to cool naturally to room temperature, take it out and cut it. Install a 180° peeling fixture on the universal testing machine, adjust the sample position, ensure that the bonding surface of the film forms a 180° angle with the stretching surface, and fix the other end of the sample to the upper fixture. Set the peeling speed to 30mm / min and start the test. After the test, record and analyze the peeling force and peeling distance curve during the peeling process to evaluate the bonding strength.
[0139] The above test results are shown in Table 1 below:
[0140] Table 1
[0141] Water vapor transmission rate Young's modulus Interfacial peel strength Example 1 <![CDATA[0.09g·mm / m 2 ·day]]> 1.1MPa <![CDATA[225J / m 2 ]]> Example 2 <![CDATA[0.19g·mm / m 2 ·day]]> 1.2MPa <![CDATA[246J / m 2 ]]> Example 3 <![CDATA[0.22g·mm / m 2 ·day]]> 0.86MPa <![CDATA[386J / m 2 ]]> Example 4 <![CDATA[3.15g·mm / m 2 ·day]]> 2.8MPa <![CDATA[212J / m 2 ]]> Example 5 <![CDATA[3.8g·mm / m 2 ·day]]> 3.3MPa <![CDATA[198J / m 2 ]]> Example 6 <![CDATA[0.18g·mm / m 2 ·day]]> 2.1MPa <![CDATA[258J / m 2 ]]> Example 7 <![CDATA[3.1g·mm / m 2 ·day]]> 1.6MPa <![CDATA[312J / m 2 ]]> Example 8 <![CDATA[0.11g·mm / m 2 ·day]]> 1.3MPa <![CDATA[285J / m 2 ]]> Example 9 <![CDATA[0.11g·mm / m 2 ·day]]> 1.2MPa <![CDATA[256J / m 2 ]]> Example 10 <![CDATA[0.14g·mm / m 2 ·day]]> 1.4MPa <![CDATA[289J / m 2 ]]> Embodiment 11 <![CDATA[0.12g·mm / m 2 ·day]]> 1.4MPa <![CDATA[312J / m 2 ]]> Example 12 <![CDATA[0.14g·mm / m 2 ·day]]> 1.7MPa <![CDATA[428J / m 2 ]]> Embodiment 13 <![CDATA[0.11g·mm / m 2 ·day]]> 1.2MPa <![CDATA[98J / m 2 ]]> Embodiment 14 <![CDATA[0.28g·mm / m 2 ·day]]> 2.3MPa <![CDATA[298J / m 2 ]]> Comparative Example 1 <![CDATA[0.18g·mm / m 2 ·day]]> 1.1MPa <![CDATA[9J / m 2 ]]> Comparative Example 2 <![CDATA[0.14g·mm / m 2 ·day]]> 1.8MPa <![CDATA[58J / m 2 ]]> Comparative Example 3 <![CDATA[0.29g·mm / m 2 ·day]]> 5.9MPa <![CDATA[272J / m 2 ]]>
[0142] It can be seen from the above test results that the flexible packaging film prepared by the embodiments of the present application exhibits excellent comprehensive performance: it not only has an extremely low water vapor permeability, ensuring excellent barrier properties, but also has good elasticity and interface adhesion ability. These characteristics together give the film reliability and practicality in flexible packaging applications. Among them, since the polar polymers used in Examples 4, 5 and 7 have relatively high water permeabilities relative to the polar polymers used in other embodiments and comparative examples, the water vapor permeability is relatively large. In the comparative case of the packaging film of pure elastomeric polymer provided in Comparative Example 1 and the comparative case of polar polymer micro-domain particles uniformly distributed throughout the packaging film provided in Comparative Example 2, the interfacial peeling strength between the film and the packaging substrate is significantly reduced, and the adhesion ability of the surface is significantly reduced. In the comparative case of the polar polymer deposition in Comparative Example 3 to form a polar polymer layer, stratification occurs in the film, which will cause the stability of the film to be significantly reduced, the Young's modulus of the film to be significantly increased, and the flexibility of the film to be significantly reduced.
[0143] The above are only optional embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A flexible packaging film, characterized in that: The flexible packaging film uses an elastomeric polymer having a flexible segment and a rigid segment as a substrate, and comprises an elastomeric polymer surface and a viscoplastic surface, wherein hard phase polar polymer microdomains are discretely distributed on the viscoplastic surface.
2. The flexible packaging film according to claim 1, characterized in that: In the flexible packaging film, the doping concentration of the polar polymer microdomain increases gradually along the direction from the elastomeric polymer surface to the viscoplastic surface.
3. The flexible packaging film according to claim 1, characterized in that: In the flexible packaging film, the mass percentage of the polar polymer microdomains is 2% to 10%.
4. The flexible packaging film according to claim 1, characterized in that: The average particle size of a single polar polymer microdomain is 50 nm to 2 μm.
5. The flexible packaging film according to claim 1, characterized in that: The thickness of the flexible packaging film is 10 μm to 2 mm.
6. The flexible packaging film according to any one of claims 1 to 5, characterized in that: The elastomeric polymer includes a styrene elastomeric polymer.
7. The flexible packaging film according to claim 6, characterized in that: The elastomeric polymer includes at least one of styrene-butadiene-styrene, styrene-isoprene-styrene, styrene-ethylene-butylene-styrene, styrene-isobutylene-styrene, styrene-propylene-styrene, and styrene-ethylene-propylene-styrene.
8. The flexible packaging film according to any one of claims 1 to 5, characterized in that: The polar polymer microdomains include at least one of maleic anhydride grafted polymers and glycidyl ether grafted polymers.
9. The flexible packaging film according to claim 8, characterized in that: The polar polymer microdomains include at least one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted acrylonitrile-butadiene-styrene copolymer, and glycidyl ether grafted polypropylene.
10. A method for preparing a flexible packaging film, characterized in that: The following steps are involved: preparing a mixed slurry of an elastomeric polymer and a polar polymer; The mixed slurry is deposited on the surface of a substrate and subjected to a microscopic phase separation treatment, so that the polar polymer forms a hard phase microdomain structure distributed on the surface of one side of the film layer, and dried to obtain a flexible packaging film having an elastomeric polymer surface and a viscoplastic surface; the polar polymer microdomains are discretely distributed in the viscoplastic surface.
11. The method for preparing a flexible packaging film according to claim 10, characterized in that: The preparation method of the mixed slurry includes: a dissolution method or a melting method; and / or, the method of depositing the mixed slurry on the surface of the substrate comprises a solution casting method, a blade coating method or an extrusion coating method; And / or, the step of micro-phase separation treatment comprises: after sealing and standing for 3 hours to 6 hours, volatilizing and removing the solvent in the mixed slurry at an evaporation rate of 0.4 μm / min to 0.7 μm / min; and / or, the substrate is plasma pretreated; And / or, the drying conditions include: drying under vacuum conditions at a temperature of 80° C. to 120° C. for 12 h to 24 h.
12. The method for preparing a flexible packaging film according to claim 11, characterized in that: The steps of the dissolution method include: preparing the solution of the elastomeric polymer and the solution of the polar polymer respectively, and then blending them to obtain the mixed slurry; And / or, the melting method comprises: mixing and melting the elastomeric polymer, the plasticizer and the viscosity reducer, and then adding the polar polymer and mixing and melting to obtain the mixed slurry; And / or, the plasma pretreatment uses an argon-oxygen mixed gas, the excitation frequency is 10 MHz to 15 MHz, and the treatment time is 5 min to 15 min.
13. The method for preparing a flexible packaging film according to claim 12, characterized in that: The concentration of the elastomeric polymer solution is 50 mg / mL to 500 mg / mL; and / or, the concentration of the polar polymer solution is 0.5 mg / mL to 25 mg / mL; And / or, the temperature condition of the melting method is 140°C to 200°C; and / or, the mass ratio of the elastomeric polymer to the plasticizer and the viscosity reducer is (200-400):(20-100):(2-15); And / or, the plasticizer comprises polyisobutylene liquid rubber having an average molecular weight of 400 to 2000; And / or, the viscosity reducer includes at least one of cycloparaffin oil, paraffin oil and aromatic oil.
14. The method for preparing a flexible packaging film according to any one of claims 10 to 13, characterized in that: The mass ratio of the elastomeric polymer to the polar polymer is (100-200):(2-10); and / or, the elastomeric polymer comprises at least one of styrene-butadiene-styrene, styrene-isoprene-styrene, styrene-ethylene-butylene-styrene, styrene-isobutylene-styrene, styrene-propylene-styrene, styrene-ethylene-propylene-styrene; And / or, the polar polymer includes at least one of maleic anhydride grafted polypropylene, maleic anhydride grafted polyethylene, maleic anhydride grafted polyolefin elastomer, maleic anhydride grafted acrylonitrile-butadiene-styrene copolymer, and glycidyl ether grafted polypropylene.
15. A flexible electronic device, characterized in that: The flexible electronic device comprises the flexible packaging film according to any one of claims 1 to 4 and / or the flexible packaging film prepared by the method according to any one of claims 5 to 8.
Citation Information
Cited By
Flexible encapsulation film and preparation method therefor, and flexible electronic device
WO2026097441A1